2018
DOI: 10.3892/etm.2018.6814
|View full text |Cite
|
Sign up to set email alerts
|

PVT1 regulates inflammation and cardiac function via the MAPK/NF‑κB pathway in a sepsis model

Abstract: The aim of the present study was to investigate the role of plasmacytoma variant translocation gene 1 (PVT1) in the occurrence and development of sepsis-induced inflammation and cardiac dysfunction and its underlying mechanism. A sepsis rat model was first established by cecal ligation and puncture. The mRNA levels of PVT1 and microRNA-143 in the myocardial tissues of rats were detected by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analysis. Cardiac function, levels of myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…This requires confirmation from further studies. a previous study has demonstrated that Pvt1 was upregulated in the myocardial tissues of sepsis rats, which inhibited cardiac function and promoted the secretion of inflammatory factors via activation of the MaPK/nF-κB pathway (48). Furthermore, Pvt1 has also previously been demonstrated to be upregulated in cardiac hypertrophic model mice when compared with the sham group; while knockout of Pvt1 by siRNA significantly reduced the cardiomyocyte size (49).…”
Section: Discussionmentioning
confidence: 93%
“…This requires confirmation from further studies. a previous study has demonstrated that Pvt1 was upregulated in the myocardial tissues of sepsis rats, which inhibited cardiac function and promoted the secretion of inflammatory factors via activation of the MaPK/nF-κB pathway (48). Furthermore, Pvt1 has also previously been demonstrated to be upregulated in cardiac hypertrophic model mice when compared with the sham group; while knockout of Pvt1 by siRNA significantly reduced the cardiomyocyte size (49).…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, our data substantiated that the NF-κB signaling pathway was involved in the regulation of the PVT1/miR-23b-3p/WT1 axis in HG-induced MCs. Feng et al demonstrated that PVT1 modulated inflammatory response and cardiac function in a sepsis model through regulating the NF-κB signaling pathway [37]. Naidu et al discovered that miR-23b mediated the regulation in lung tumorigenesis via targeting the NF-κB signaling pathway [38].…”
Section: Discussionmentioning
confidence: 99%
“…PVT1 has been revealed to accelerate lipopolysaccharide (lPS)-induced septic acute kidney injury (11). PVT1 was demonstrated to impede cardiac function and facilitate the secretion of inflammatory factors in a sepsis model (12). additionally, PVT1 has been revealed to modulate the apoptosis of chondrocytes in osteoarthritis (13).…”
Section: Introductionmentioning
confidence: 99%